THE USE OF GAMIFICATION METHOD TO IMPROVE NINTH GRADE STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT AT SMP NEGERI 7 PEMATANG SIANTAR - Isabel selmiola sabrina; Dwi Angeli Pardede; Gabriella Pardede; Bella Sonia Sianturi; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Reading comprehension plays a crucial role in English language learning, as it enables students to understand written texts and construct meaning effectively. However, many EFL students still experience difficulties in comprehending descriptive texts due to low motivation and the continued use of teachercentered instructional practices. Although previous studies have reported positive outcomes of gamification in language learning, limited research has specifically examined its effectiveness in improving students’ reading comprehension of descriptive texts in junior high school contexts. Therefore, this study aims to investigate the effectiveness of the Gamification Method in enhancing ninth-grade students’ reading comprehension at SMP Negeri 7 Pematangsiantar. A quasi-experimental design was employed, involving an experimental group taught using gamified activities through Quizizz and Kahoot, and a control group taught using conventional methods. Each group consisted of 30 students, and data were collected through pre-tests and posttests. The findings revealed that both groups showed improvement after the treatment; however, the experimental group achieved a higher post-test mean score (85.17) than the control group (83.17). The Independent Samples t-test result indicated a statistically significant difference between the two groups (p < 0.05). In conclusion, the study confirms that the Gamification Method is effective in improving students’ reading comprehension of descriptive texts by increasing their motivation, engagement, and learning achievement.. Keyword : Reading Comprehension, Descriptive Text, Gamification Method, EFL Students, Junior High School